Choroid plexus enlargement in paediatric multiple sclerosis: clinical relevance and effect of sex. Issue 3 (9th November 2022) - Margoni, Monica; Gueye, Mor; Meani, Alessandro; Pagani, Elisabetta; Moiola, Lucia; Preziosa, Paolo; Filippi, Massimo; Rocca, Maria A
Abstract : Background: Choroid plexus (CP) enlargement has been suggested as a reliable marker of neuroinflammation in adult multiple sclerosis (MS). We investigated CP volume in patients with paediatric MS compared with matched healthy controls (HC), possible sex-related effect, and the associations with clinical and structural MRI variables. Methods: Brain 3.0 T dual-echo and three-dimensional (3D) T1-weighted sequences were selected retrospectively from 69 patients with paediatric MS and 23 age-matched and sex-matched HC. CP volume was manually obtained from 3D T1-weighted scans by two expert raters. Results: CP segmentation was highly reproducible (intraobserver agreement: rater I=0.963, rater II=0.958; interobserver agreement=0.968). Compared with HC, patients with paediatric MS showed higher normalised CP volume (p<0.001). Both female and male patients with paediatric MS showed higher normalised CP volume compared with sex-matched HC (women: p<0.001 and men: p=0.021), with a significant disease×sex interaction (p=0.040). In patients with MS, a higher normalised CP volume was significantly associated with higher brain lesional volume (β=0.252, p=0.017), larger lateral ventricle volume (β=0.470, false discovery rate (FDR)-p<0.001), lower normalised brain volume (β=−0.413, FDR-p=0.002) and lower normalised thalamic volume (β=0.291, FDR-p=0.046). No associations with disease duration, Expanded Disability Status Scale score, normalised cortical and white matter volumes were found (FDR-p≥0.172). A significant effect of the disease in the negative association between normalised volumes of CP and thalami was observed (FDR-p=0.046). Conclusions: CP enlargement occurs in paediatric MS, suggesting its early involvement in the pathophysiology of the disease. The higher CP volume, which is found especially in female patients, supports the hypothesis of sex-related differences occurring already in paediatric MS.